The Influence of Conversational AI on Consumer Behavior and Counterfactual Thinking: A Systematic Review - Bouhlal, Hind; Belahcen, Noureddine (European Scientific Journal, ESJ, 2025)
This document evaluates the development and importance of conversational AI, chatbots, and virtual assistants in shaping human behavior and decision-making,particularly in the context of e-commerce. It is designed to investigate the impact of AI on the personalization of user experiences, and maps how the automation of decision-making affects cognitive processes like counterfactual thinking and regret. The findings sugest that while conversational AI enhances the shopping experience through personalized product recommendations, it can also trigger cognitive biases such as regret by exposing consumers to alternative options, leading them to reconsider their initial choices. This raises concerns about AI risk mitigation, particularly regarding transparency, psychographic profiling,and the emotional influence of AI-driven decision-making. Importantly,the study highlights that consumers do not inherently dislike AI; rather,they seek a more ethical and culturally aware approach to its implementation. A responsible AI design could not only improve user experience but also strengthen consumer trust in AI-driven products and services.To fully understand tese dynamics, longitudinal studies are needed to assess the long-term effects of conversational AI on consumer satisfaction, loyalty,and decision-making. Additionally,cross-cultural comparisons will provide deeper insights into how consumer perceptions and interactions with AI vary across different markets.